Environmental Education in a High School Biology Class: Knowing and Appreciating Nature - Bonotto, Dalva Maria Bianchini [UNESP] (My University, 2012)
The call for changes in the situation of environmental degradation that characterizes the contemporary world has come from diverse sectors of society, and education has an important role to play. To achieve this goal, educational efforts must contemplate the natural, as well as the cultural aspects of the environment. The theme can be addressed at the different levels of formal teaching, by adopting an interdisciplinary approach that addresses the aesthetic dimension of natural and man-made environments. The purpose of this book is to present the analysis of an intervention, developed in biology classes related to the environmental thematic focusing on ecological knowledge and aesthetic dimension of natural and man-made environments. The author analyzes the engagement and participation of high school students and some possibilities and limits for the development of such activities. © 2013 by Nova Science Publishers, Inc. All rights reserved.